Accessibility via metadata in a semantic web-driven Content Management System. (7th February 2007) - Garcia-Robles, Rocio; Cabrerizo, Alvaro; Prieto, Juan Antonio; Del Rio, Fernando Diaz; , Anton Civit
For promoting accessibility, not only binding the W3C-WCAG, but also the discovery of material having appropriate accessibility support and the adjustment of control and display of resources, are important. Both challenges are addressed by the IMS Consortium. In this paper, we survey how far IMS accessibility specifications cover WCAG. We argue why using a semantic framework for describing textual and contextual information in a standardised manner could promote accessibility and reusability. Finally, we explain how some accessibility issues are addressed by XimetriX's ximDEX, a semantic-web CMS. A plan to integrate accessibility specifications and contextual description tools into that CMS is proposed.